2016
DOI: 10.1111/1744-9987.12476
|View full text |Cite
|
Sign up to set email alerts
|

Monocarboxylate Transporter‐1 Mediates the Protective Effects of Neutral‐pH Bicarbonate/Lactate‐Buffered Peritoneal Dialysis Fluid on Cell Viability and Apoptosis

Abstract: We investigated the effects of bicarbonate/lactate-buffered peritoneal dialysis fluid (B/L-PDF) and lactate-buffered PDF (L-PDF) on cell viability and apoptosis, focusing on monocarboxylate transporters (MCTs). MCT-1 transports lactate into cells. Cell viability and apoptosis of human peritoneal mesothelial cells (HPMCs) were examined by water-soluble tetrazolium salt-1 and TUNEL assays, respectively. The relative number of viable HPMCs was significantly decreased by L-PDF at 48 h (8.8 ± 0.4%) compared with ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…One report used the same two PDFs we used and found that bicarbonate/lactate PDF was less toxic to cell viability and apoptosis of PMCs than lactate PDF [12]. In addition, a clinical study [13] reported that Fibrin degradation products and vascular endothelial growth factor concentrations in effluent were lower when using bicarbonate/lactate PDF than when using lactate PDF.…”
Section: Discussionmentioning
confidence: 98%
“…One report used the same two PDFs we used and found that bicarbonate/lactate PDF was less toxic to cell viability and apoptosis of PMCs than lactate PDF [12]. In addition, a clinical study [13] reported that Fibrin degradation products and vascular endothelial growth factor concentrations in effluent were lower when using bicarbonate/lactate PDF than when using lactate PDF.…”
Section: Discussionmentioning
confidence: 98%
“…Low-glucose degradation product bicarbonate/lactatebuffered solutions are reported to have less cell toxicity and superior cell viability in vitro, and less neoangiogenesis and impaired ultrafiltration in rat models of PD, as compared with low pH lactate-buffered solutions [8][9][10]. Kuma et al reported a lactate-induced reduction in cell viability, showing that apoptosis of human peritoneal mesothelial cells was markedly induced by L-PDFs, but not by B/L-PDFs, which was attenuated by knockdown of monocarboxylate transporter-1, a cell membrane lactate transporter [11].…”
Section: Introductionmentioning
confidence: 99%